Increased Price Markup from Union Coordination. OECD Panel Evidence - Roger Bjørnstad; Kjartan Øren Kalstad (Statistics Norway, Research Department, 2006)
Existing literature have focused on the influence of institutional factors on wage determination when explaining the prolonged cross-country differences in unemployment. Although coordination of wage bargaining probably affects entry barriers and competition in product markets as well, research on price determination has typically not considered such factors. In this paper, an imperfect competition model - where the price markup depends on coordination of wage bargaining (and relative prices) - is set up and estimated on a panel of 15 OECD-countries. We derive a hypothesis that coordination has two separate effects on prices, i.e. an indirect effect through its effect on wages and a direct effect on the price markup. The estimates show that when we correct for the effect of coordination on wages, consumer prices may be as much as 21 percent higher in countries like Italy, the Netherlands, Ireland, Austria and Norway as compared to Canada, the US and the UK, due to the effect of coordination on the price markup. Since coordination probably has a dampening effect on wages, this may explain why many researchers have been unable to find any clear effect of coordination on unemployment in reduced form analysis.
Keywords: C23; E31; J51; 330; Imperfect competition model; price markup; labor market institutions; unemployment; panel data model.